Single blind randomised controlled trial of GAME (Goals ‐ Activity ‐ Motor Enrichment) in infants at high risk of cerebral palsy. (August 2016) - Morgan, Catherine; Novak, Iona; Dale, Russell C.; Guzzetta, Andrea; Badawi, Nadia
Highlights: Infants at high risk of CP were accurately identified using the General Movements Assessment or MRI. GAME intervention led to improved motor outcomes when compared to standard care. GAME participants had higher cognition scores at 12 months of age. Abstract: Background: Cerebral palsy (CP) is caused by a lesion in the developing infant brain. Recent neuroplasticity literature suggests that intensive, task-specific intervention ought to commence early, during the critical period of neural development. Aims: To determine whether "GAME" (Goals ‐ Activity ‐ Motor Enrichment), a motor learning, environmental enrichment intervention, is effective for improving motor skills in infants at high risk of CP. Methods and procedures: Single blind randomised controlled trial of GAME versus standard care. Primary outcome was motor skills on the Peabody Developmental Motor Scales-2 (PDMS-2). Secondary outcomes included Canadian Occupational Performance Measure (COPM), Bayley Scales of Infant and Toddler Development (BSID-III) and Gross Motor Function Measure-66 (GMFM-66). Outcome assessors were masked to group allocation and data analyzed with multiple regression. Outcomes and results: All n = 30 infants enrolled received the assigned intervention until 16 weeks post enrolment. At 12 months of age, n = 26 completed assessments. Significant between group differences were found in raw scores on the PDMS-2 in favour of GAME (B = 20.71, 95%CI 1.66‐39.76, p = 0. 03) and at 12 months on the total motor quotient (B = 8.29, 95%CI 0.13‐16.45, p = 0.05). Significant between group differences favored GAME participants at 12 months on the cognitive scale of the BSID-III and satisfaction scores on the COPM. Conclusion: GAME intervention resulted in advanced motor and cognitive outcomes when compared with standard care.